Legal issues in rendering mental health care in Kazakhstan - Жаппарова, A. (Право и государство, 2021)
One of the basic human rights is the right of citizens for protecting their health and receiving qualified medical care. The issues of human mental health refer to the actual problems of contemporary medical science. The article is aimed, on the one hand, to focus the attention on the current situation in the sphere of mental health services and, on the other hand, to show the correlation of the national legislation in this sphere with the existing international standards. The Article was written based on comparative analysis and expert estimation methods. The right for the highest achievable standard of health imposes an obligation on the state to respect human rights, to protect against violation and fulfill all conditions necessary for the implementation of these rights. The basic principles of treating persons with mental disorders are enshrined in the Principles for the Protection of Persons with Mental Illnesses and the Improvement of Mental Health Care. Mental health services do not reduce themselves to medical care only. They cover a broader legal relationship. A medical opinion that a person has a mental disorder can significantly affect the restriction of their rights - involuntary treatment, recognition as incapacitated, insane or partially sane, inability to engage in certain professional activities, etc. Key findings: National “medical” legislation has become as close to international standards as possible. In the provision of mental health services there has been a definite step forward compared with the Soviet past. This is mainly due to the human rights principles of the 2009 and 2020 set out in the Codes of the Republic of Kazakhstan “On Public Health and the Health Care System”. The legal framework within which mental health care is to be provided has been enshrined in legislation. The actions of healthcare professionals have become strictly regulated. Providing medical care, with the exception of cases provided for by law, requires informed consent. But, despite the positive developments in legal regulation, the actual situation of persons with mental disorders staying in healthcare institutions can hardly be considered satisfactory. The results of visits by National Preventive Mechanism members of closed medical organizations, as well as appeals by patients themselves to the Ombudsman for Human Rights in the Republic of Kazakhstan, also point to this. In order to overcome the stigma towards persons with mental and behavioral disorders, it is necessary to bring domestic legislation into line with the provisions of Principle 1 on the protection of mentally ill persons and the improvement of mental health care, which will ensure a humane and respectful attitude towards the dignity of a person. The improvement of legislation is also required in ensuring the socio-economic guarantees of such persons staying in medical organizations.
Keywords: mental health services, patient, health professionals, compulsory treatment, right for information, right for consent, voluntary treatment, non-discrimination